2017
DOI: 10.3389/fnhum.2017.00170
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of Human Balance Control: A Systematic Review

Abstract: This review examined 83 articles using neuroimaging modalities to investigate the neural correlates underlying static and dynamic human balance control, with aims to support future mobile neuroimaging research in the balance control domain. Furthermore, this review analyzed the mobility of the neuroimaging hardware and research paradigms as well as the analytical methodology to identify and remove movement artifact in the acquired brain signal. We found that the majority of static balance control tasks utilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(123 citation statements)
references
References 137 publications
(268 reference statements)
4
114
0
5
Order By: Relevance
“…From a motor control perspective, the DLPFC has been implicated in planning of action motor sequences and allocating attentional resources (Kaller, Rahm, Spreer, Weiller, & Unterrainer, ; Unterrainer & Owen, ). Therefore, the greater increase in bilateral DLPFC activation with greater sensory demands during the balance tasks in older compared to younger adults may be indicative of greater reliance on executive function, indirect locomotor pathways (Hamacher, Herold, Wiegel, Hamacher, & Schega, ; Herold, Wiegel et al., ; Wittenberg et al., ), and reduced automaticity in balance control (Paul, Ada, & Canning, ). The indirect locomotor pathway forms part of the corticobasal ganglia network that is involved with preventing unwanted muscle contractions from competing with voluntary movements (Nambu, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From a motor control perspective, the DLPFC has been implicated in planning of action motor sequences and allocating attentional resources (Kaller, Rahm, Spreer, Weiller, & Unterrainer, ; Unterrainer & Owen, ). Therefore, the greater increase in bilateral DLPFC activation with greater sensory demands during the balance tasks in older compared to younger adults may be indicative of greater reliance on executive function, indirect locomotor pathways (Hamacher, Herold, Wiegel, Hamacher, & Schega, ; Herold, Wiegel et al., ; Wittenberg et al., ), and reduced automaticity in balance control (Paul, Ada, & Canning, ). The indirect locomotor pathway forms part of the corticobasal ganglia network that is involved with preventing unwanted muscle contractions from competing with voluntary movements (Nambu, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the ecological validity of using an imagined task during fMRI is questionable as it only provides an implied measure of brain response during actual upright body movements or postural control. Recent systematic reviews have highlighted the ability to apply fNIRS as a neuroimaging technique to quantify the cortical control of static and dynamic forms of balance and gait (Herold, Wiegel, et al., ; Wittenberg, Thompson, Nam, & Franz, ). In this context, fNIRS may offer an advantageous alternative to fMRI due to reduced physical constraints and greater portability (Herold, Wiegel et al., ; Wittenberg et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postural control requires the complex interaction of different structures within the somatosensory system to maintain and recover balance during the performance of sport and everyday activities (Shumway-Cook and Woollacott 2012). Several electroencephalographic (EEG) studies provide evidence that postural control involves the activity of cortical structures under static (e.g., unperturbed/perturbed upright stance) (Edwards et al 2018;HĂŒlsdĂŒnker et al 2015a, b;Peterson and Ferris 2018;Slobounov et al 2009;Solis-Escalante et al 2019;Varghese et al 2014) and dynamic conditions (e.g., unperturbed/perturbed walking) (Peterson and Ferris 2018;Sipp et al 2013;Wagner et al 2016, for a review see Wittenberg et al 2017). Most of these studies observed altered activation that contributed to postural control across different cortical areas located near anterior cingulate, dorsolateral prefrontal cortex, supplementary motor areas, parietal, and temporal cortices on either the channel (Edwards et al 2018;HĂŒlsdĂŒnker et al 2015a, b) or the source level (Peterson and Ferris 2018; Communicated by Francesco Lacquaniti.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data-driven analysis of fMRI has elucidated motor (lobules I-VI; lobule VIII), and non-motor (lobules VI-Crus I; lobules Crus II-VIIB; lobules IX-X) attentional/executive as well as default mode regions of the cerebellar function [24]. Here, prefrontal, premotor, supplementary motor, and parietal cortex have been found involved with standing balance control in hemiplegic stroke patients [25]. Although cerebellar TMS provided a method to probe the cerebellar-M1 connections in our prior work [14]; however, it was found challenging in a rehabilitation setting.…”
Section: Introductionmentioning
confidence: 90%